Turbulent waters : cross-border finance and international governance - Bryant, Ralph C., 1938- (Brookings Institution Press, 2003)
"Bryant explains basic concepts about financial activity and collective governance, distills their international dimensions, and enables general readers to acquire a solid grasp of the key policy issues that national governments must resolve. He provides fresh insights about what is often termed the international financial architecture. But he also casts his net far wider: the book's ambitious goal is no less than to outline a pragmatically sound vision for the evolution of international government for the world economy and financial system."--Jacket